Safety and effectiveness of baloxavir marboxil and oseltamivir for influenza in children: a real-world retrospective study in China - Ge, Xilin; Chen, Yang; Wu, Wei; Lu, Jinmiao; Wang, Yi; Li, Zhiping (Frontiers in Pediatrics, 2024)
Objectives: To evaluate the safety and effectiveness of baloxavir marboxil (baloxavir) and oseltamivir in pediatric influenza patients in China.: Patients filling a prescription for baloxavir or oseltamivir within 48 hours following an influenza-related outpatient visit were identified in Children's Hospital of Fudan University in China between March 2023 and December 2023. Outcomes were assessed after antiviral treatment and included the incidence of adverse reactions and the duration of fever and other flu symptoms.Results: A total of 1430 patients infected with influenza A were collected and 865 patients (baloxavir: n =420; oseltamivir: n = 445) finally included. The incidence of adverse reactions of nausea and vomiting was significantly different between the baloxavir group (2.38%) and the oseltamivir group (12.13%)(P<0.001, OR = 4.2526, 95%CI [2.0549, 9.6080]). No differences in other adverse reactions were observed between the two groups. The mean duration of fever in baloxavir group (1.43d) was significantly shorter than that in oseltamivir group (2.31d) , significantly (P<0.001, 95%CI [0.7815, 0.9917]). There were no differences in the mean duration of nasal congestion and runny nose, sore throat, cough, and muscle soreness inbetween two groups.The incidence of nausea and vomiting is lower with baloxavir than withcompared to oseltamivir, and the duration for complete fever reduction is shorter with baloxavir than with oseltamivir. The results indicate that baloxavir is well tolerated and effective in Chinese children.